2016
DOI: 10.3892/br.2016.581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-intensity focused ultrasound on endothelin-1, nitrogen monoxide and oxytocin receptor in the uterine tissues of Sprague-Dawley rats following abortion

Abstract: Abstract. The aim of the present study was to investigate the effect of low-intensity focused ultrasound on endothelin-1 (ET-1), nitrogen monoxide (NO) and oxytocin receptor (OXTR) levels in the uterine tissues of Sprague-Dawley (SD) rats following abortion. A total of 30 SD rats undergoing complete abortion were randomly divided into ultrasound irradiation and sham irradiation groups (15 rats per group). The rats in the ultrasound irradiation group were treated with low-intensity ultrasound (sound intensity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…2. Ultrasound may upregulate the expression of uterine endometrium and myometrium oxytocin receptors and enhance the uterine contraction response at a molecular level [ 18 , 19 ]. 3.…”
Section: Discussionmentioning
confidence: 99%
“…2. Ultrasound may upregulate the expression of uterine endometrium and myometrium oxytocin receptors and enhance the uterine contraction response at a molecular level [ 18 , 19 ]. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary results showed that the participants who received LIFUS treatment had a faster decline rate and higher decline index than those who received sham treatment, indicating that LIFUS was effective in the treatment of uterine contraction. The biological effects of LIFUS mechanical stimulation, as well as the physical advantages of high penetration and focusing, make the application of LIFUS for uterine involution comfortable and painless (14,15). A slight change was observed in the rate of fundus descent.…”
Section: Discussionmentioning
confidence: 99%
“…and oxytocin (PGR and OXTR), involved in involution processes, were observed in metritic primiparous compared with healthy primiparous (P < 0.05). It has been hypothesized that increasing the expression of OXTR in postpartum uterine cells may help in managing incomplete uterine involution [36]. It is known that in mammals, signaling oxytocin via OXTR in the uterus results in the initiation of parturition [37].…”
Section: Accepted Manuscriptmentioning
confidence: 99%